Moderating Effects of the Ego-Energy in Relation to Stress, Drinking Motives, and Depression in Korean Adult Males - Yoon, Doohah; An, Hyonggin (Frontiers in Psychology, 2021)
Although there have been numerous studies using stress and coping theories to explain the relationship between stress, drinking motives, and depression, very few of them have attempted to verify these theories against adult male data. There is also a shortage of Korean studies, both theoretical and empirical, on the ego-energy’s role as a moderating variable in the relationship between stress, drinking motives, and depression. This study uses a multiple-group analysis to investigate the moderating effects of the ego-energy on the aforementioned relationship in adult males. A transactional analysis tool showing the total amount of ego-energy called Ego-gram was used in the study. The tool reflects personality traits based on ego-energy state structural and functional analysis. The researchers collected empirical data to test the research model by conducting an online survey of adult males aged 20–50, residing in seven metropolitan cities, and the Gyeonggi province. The survey yielded 567 samples. The data were then analyzed through structural equation modeling (SEM) to understand the relationship between various factors. The results showed that, first, stress was positively correlated with drinking motives. Second, drinking motives had some influence on depression. Third, stress, drinking motives, and depression had statistically significant relationships between low ego-energy and high ego-energy groups. Overall, the study found a difference between the two ego-energy groups concerning the relationship between stress, drinking motives, and depression. Based on these results, practical implications were discussed as to how to strengthen the ego-energy, while also presenting future research directions to shed light on the precise mechanism of depression. This study is significant for exploring ways in which adult males cope with and prevent stress and depression, while also offering basic data for improving adult males’ mental and physical health. The study is also significant for calling attention to the necessity of developing various health and wellness programs adapted to the needs of this specific population segment while providing data that may serve as the basis for developing such programs.